Developing strategies for alleviating caregiver burden among informal caregivers of persons with severe mental disorders in Bushbuckridge, Mpumalanga province - Silaule, Olindah Mkhonto (University of the Witwatersrand, Johannesburg, 2025)
Background: Globally, implementation of deinstitutionalisation led to a shift from institutional to community care of persons with severe mental disorders. This move calls for informal caregivers including families, relatives, friends, or neighbours to become key role players in the care and management of persons with severe mental disorders. The role of informal caregiving results in stress that consequently leads to caregiver burden. In South Africa, limited evidence exists on the extent of the burden experienced by the informal caregivers of persons with severe mental disorders and strategies for supporting these informal caregivers in their role are lacking. This study aimed to explore the burden of care to inform the development of strategies for alleviating burden among informal caregivers of persons with severe mental disorders in Bushbuckridge, Mpumalanga province. Methods: This study used a three-phased mixed methods approach with a multiphase design to facilitate a comprehensive investigation of caregiver burden among informal caregivers and to develop the multilevel strategies for alleviating the burden. Sequential and concurrent methods were combined to collect quantitative and qualitative data across five studies that were conducted to address the study objectives. Results: The established extent of burden revealed that most informal caregivers (44.7%) reported moderate-to-severe levels of objective burden, and 35.9% reported moderate-to-moderate levels of subjective burdens. Objective burden levels were significantly associated with age, gender and residence (p = 0.025, p = 0.034, and p = 0.038, respectively), while subjective burden was significantly associated with daily caregiving (p = 0.012). The exploration of lived experiences revealed that most informal caregivers experienced burden with subsequent impact on their emotional, mental, and physical health. The subsequent burdens were attributed to dealing with the chronic nature of severe mental disorders, role and financial strain, and stigmatisation from family and community. To deal with their caregiving demands informal caregivers expressed reliance on their internal resources, including resilience and resourcefulness. Expressed support needs included access to mental health services, and empowerment and social support from family, government, and religious and community organisations. The findings identified the need for conducting health screenings among the informal caregivers, as well as the need for strategies to support informal caregivers to complement their internal coping resources. The findings of the scoping review revealed that most studies were conducted in Asian countries. Psychoeducation and support group interventions were identified as predominant strategies for alleviating caregiver burden. The service provider’s perspectives revealed that the current state of formal and informal community mental health services is inadequate to meet the needs of the informal caregivers. Conclusion: The study’s findings informed the development of strategies for alleviating caregiver burden among informal caregivers in a low-resourced setting. The complexity of caregiver burden requires multilevel strategies, namely caregiver-driven, health worker-driven, community-based, intersectoral, policy, and legislature strategies across the individual, interpersonal, organisational, community, and policy levels. Caregiver empowerment, family and peer support, development of caregiver-orientated institution and community-based services, task sharing, and task shifting were identified as overriding strategies relevant for alleviating informal caregiver burden in a low- resourced setting
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa. May,2024
Keywords: Caregiver burden; Caregiver strain; Informal caregiver; Informal carers; Severe mental disorders; Chronic mental disorders; Rural South Africa; UCTD; SDG-3: Good health and well-being